IMPELEMENTASI METODE HARRIS BENEDICT PADA SISTEM INFORMASI PENGHITUNGAN GIZI REMAJA BERBASIS WEBSITE - Guntara, Arya; Frencis Matheos Sarimole (CV. Hawari, 2021)
The teenage period is the peak stage of the growth period of a person's weight and height. This growth process requires sufficient nutritional support. Teenagers who have adequate nutritional intake will have a healthy body condition, rarely experience pain so that activities at home and at school will run smoothly. Lack of adolescent knowledge to know the nutritional needs in the body, can result in inhibition of the growth process. There needs to be a nutrition education for teenagers. Adolescents need knowledge about the calculation of nutritional adequacy. Utilization of information technology is widely used as a tool of convenience and aids in daily activities. With the above problems, an information system is needed in providing knowledge to adolescents about nutritional needs in their bodies. Information systems are built with PHP and Mysql and counting nutritional needs using harris benedict methods. The Harris Benedict method is a way to count the number of calories a person needs. The programming languages used for the creation of this application are PHP and MySQL for databases. Based on the results of the study, this application can help parents to find out the nutritional needs of their children who are teenagers online.